The generation mechanism of cold eddies and the related heat flux exchanges in the upper ocean during two sequential tropical cyclones - Shen, Zheyue; Zhang, Shuwen (Frontiers in Marine Science, 2022)
The impacts of two sequential tropical cyclones (TCs), Kyarr and Maha, [from October 24 to November 06, 2019, over the Arabian Sea (AS)] on upper ocean environments were investigated using multiple satellite observations, Argo float profiles and numerical model outputs. To obtain a realistic TC strength, the Weather Research and Forecasting (WRF) model was used to reproduce Kyarr and Maha. During Kyarr and Maha, three distinct cold patches were observed at the sea surface with a maximum sea surface cooling of approximately 5°C. The comparison between WRF model simulation results and ERA5 wind field showed that the WRF model simulation indicated high simulation accuracy with respect to the SST decrease in the AS under the influence of Kyarr and Maha’s wind stress curls. Meanwhile, concentration of chlorophyll a (chl-a) and positive relative vorticity of sea surface also appeared in the three cold patch areas. Through the use of eddy detection algorithms, three mesoscale cold cyclonic eddies were identified along the track of TC Kyarr, and the locations of these cold eddies were highly correlated with three obvious negative sea surface height anomalies (SSHAs). The radii of the three cold eddies were 69 km, 50 km, and 41 km. With a focus on the thermodynamic responses of the three cold eddy fields to Kyarr and Maha, the central regions of the three cold eddies were explored. The central regions of the three cold eddies exhibited relatively shallow mixed-layer depths (MLDs) and low mixed-layer temperatures (MLTs). The depth integrated heat (DIH) content was also calculated to explore the heat flux exchanges occurring in different layers in the upper 200 m of the centre of each eddy. The results showed that DIH in each eddy centre varied by one order of magnitude, accounting for between 127.3 MJ m-2 and 1220.0 MJ m-2 of heat loss. This study suggests that the effect of long forcing time on intense positive wind stress curls can produce upwelling caused by Ekman response, which is the main influencing factor of the three cold eddies generation mechanism. At the same time, the positive relative vorticity injected into the sea surface also has some contribution. TC-induced vertical mixing and upwelling (strengthened by unstable structures inside the cold eddies) cause substantial redistribution of the DIH, and related heat flux exchanges at different layers occur in the eddy fields.